DEGUM Recommendations on Infection Prevention in Ultrasound and Endoscopic Ultrasound - Müller, Thomas; Martiny, Heike; Merz, Eberhard; Döffert, Jens; Wüstner, Matthias; Lessel, Wolfgang; Heynemann, Hans; Enzmann, Thomas; Dudwiesus, Heiko; Nuernberg, Dieter; Tesch, Christian; Weber, Marc André; Krishnabhakdi, Siegfried; Heil, Jörg; Wree, Alexander; Jenssen, Christian (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Microbial contamination of ultrasound probes for percutaneous or endoscopic use is common. However, infectious diseases caused by transmission of microorganisms by US procedures have rarely been reported. In Germany, legal regulations address hygiene in ultrasound procedures. Based on these regulations and the available literature, an expert panel of the German Society of Ultrasound in Medicine (DEGUM) has formulated sophisticated recommendations on hygienic measures in percutaneous and endoscopic US, including US-guided interventions.Mikrobielle Kontaminationen von Schallköpfen, kutan oder endokavitär angewandt, sind häufig, tatsächliche Infektionen nach Sonografien werden jedoch nur kasuistisch berichtet. In Deutschland existieren rechtliche Vorschriften zur Schallkopfhygiene. Ein Expertengremium der DEGUM hat vor dem Hintergrund der Vorschriften und der verfügbaren Literatur differenzierte Empfehlungen zur Hygiene in der Sonografie und der Endosonografie, einschließlich der ultraschallgestützten Interventionen, formuliert.
Keywords: ultrasound; infection; intervention; disinfection; endoscopic ultrasound